The Transformative Impact of Workplace Spirituality Training on Teacher Performance in Islamic Educational Institutions: An Experimental Study - Muhammad Egi Rahmadi; Ahmad Razak; Ahmad Yasser Mansyur (RADJA PUBLIKA, 2025)
This study aims to examine the effectiveness of workplace spirituality training in improving teacher performance at SMP IMIM Putra YASDIC IMIM. Educational digitalization through the Merdeka Mengajar Platform (PMM) was found to trigger administrative burdens and work-related stress, which have an effect on the decline in teacher performance. Using a quasi-experimental design (pretest posttest control group design), the study involved 15 teachers who were divided into experimental and control groups. Performance was measured through the results of academic supervision focusing on instructional planning and learning process aspects. Data analysis employed Independent and Paired Sample t-Tests. The results showed a very significant improvement in performance in the experimental group by 96.8% (scores increased from 56.13 to 110.50) with a very large effect size (Cohen’s d = -3.847), while the control group tended to remain stagnant. It is concluded that strengthening the dimensions of work meaning, sense of togetherness, and alignment with Islamic values is effective in transforming teachers’ intrinsic motivation and mental resilience, which directly has an effect on the improvement of instructional quality in the classroom. Keywords: Spiritual Training, Workplace Spirituality, Teacher Performance, Academic Supervision, Islamic Education.